Multi-optical signal channel gold nanoclusters and their application in heavy metal ions sensing arrays. Issue 8 (2nd February 2021) - Gui, Yunyun; Wang, Yihe; He, Chiyang; Tan, Zhouqing; Gao, Lingfeng; Li, Wei; Bi, Huiting
Abstract : Novel multi-optical signal channel gold nanoclusters (MS-AuNCs) with CL and FL properties were designed and prepared by a one-pot method. Then the CL and FL spectra of MS-AuNCs were applied to the sensing array for heavy metal ion differentiation. Abstract : To improve the performance of an array-based sensing system, a novel one-pot method was designed to prepare multi-optical signal channel gold nanoclusters (MS-AuNCs), including chemiluminescence (CL) and fluorescence (FL). And multi parameters were extracted from the CL and FL spectra of MS-AuNCs to realize the excellent performance of sensing arrays for heavy metal ion differentiation. In this synthetic strategy, 11-mercaptoundecanoic acid (MUA) was used as the capping agent to form Au(i )–thiol complexes first. Then luminol was introduced as a reductant to reduce the Au(i )–thiol complexes and as a chemiluminescent reagent to form MS-AuNCs. Compared with previous methods for preparing luminescent functionalized nanoparticles, the proposed method could obtain functionalized nanoparticles with multi-optical signal channels in one step and is much simple. The obtained MS-AuNCs exhibited excellent CL performance when reacting with hydrogen dioxide. The peak position of the MS-AuNCs FL emission spectra does not shift as increasing excitation wavelengths. The bright orange FL of MS-AuNCs was strong enough to be seen with naked eye. Based on five parameters extracted from the CL and FL spectra of MS-AuNCs, one sensing array was developed for distinguishing heavy metal ions. The sensing strategy could differentiate seven heavy metal ions with different concentrations, including Al 3+, Co 2+, Cr 3+, Cu 2+, Hg 2+, Pb 2+ and Zn 2+ . Moreover, novel multi-optical signal channel gold nanoclusters were obtained for the first time in this work, which may find more promising applications in fields such as bioassays and bioimaging.